HUBUNGAN MOTIVASI DENGAN KEPERCAYAAN DIRI ATLET SEKOLAH SEPAKBOLA CIKAL FC KAB. MUSI RAWAS - Suhdy, Muhammad; Erick Salman (Silampari Jurnal Olahraga, 2022)
This study aims to determine the relationship between motivation and self- confidence of soccer athletes Cikal FC, Musi Rawas Regency. The problem in this study is that there are still many athletes who lack motivation and athletes' self-confidence is not optimal. The method used in this study is a method using a correlational approach. Determination of the sample was carried out using a total sampling technique from a population of 24 football athletes from Cikal FC, Musi Rawas Regency. Based on the data analysis technique that uses the moment correlation, the increase in the correlation between motivation and self-confidence is 0.844, this figure is included in the category of very good correlation. Based on the t-test analysis at the significance level = 0.05, obtained tcount (10.021) > ttable (2.074). Thus, what is proposed in this study can be accepted as true, so it can be said that there is a significant relationship between self- motivation and soccer athletes Cikal FC, Musi Rawas Regency. The results of the coefficient of determination obtained the magnitude of the relationship between motivation and self-confidence is 71.23%.